Analisis Peran Ganda Karyawati Pada Perusahaan Daerah Bank Perekonomian Rakyat Bahteramas - Wa Ode Ayinu Tsabita; Andi Basru Wawo; Muh. Nur (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This study aims to determine and analyze (1) Describe and analyze the work mechanism as a housewife and as an employee of BPR Bahteramas (2) Describe and analyze the Dual Role experienced during being a female employee at BPR Bahteramas. The analysis tool used is the Interactive Model Analysis from Miles and Huberman, which divides the steps in data analysis activities into several parts, namely data collection, data reduction, data presentation, and conclusion drawing or verification. Based on the results of the study, it can be concluded that dual role is a phenomenon commonly faced by individuals, especially women, in everyday life. At BPR Bahteramas, female employees must face the demands of dual roles because they must carry out their roles as professional workers at work while fulfilling their responsibilities and roles as mothers, wives, or family members in the home environment. This dual role brings a number of pressures and challenges as they have to strike the right balance between the responsibilities and expectations of both roles.